Epidemiology and outcomes of Carbapenem-resistant Enterobacterales infection in high-risk patients in Saudi Arabia - Alraddadi, Basem M.; Heaphy, Emily L. G.; Almaghrabi, Reem; Althawadi, Sahar; Alshahrani, Ahmad M.; Almosallam, Salma; Alraddadi, Abdullah; Hefni, Lama; Almannaei, Mooza S.; Bahabri, Ibrahim; Taha, Rabab; Alamoudi, Ebtihal; et al. (Frontiers in Microbiology, 2025)
IntroductionSolid organ transplant (SOT) recipients, bone marrow transplant (BMT) recipients, and patients with hematological malignancies experience increased morbidity due to infections caused by multidrug-resistant, Carbapenem-resistant Enterobacterales (CRE). The current study aimed to further describe the epidemiology and outcomes associated with CRE infection in high-risk SOT and BMT recipients and in patients with hematological malignancies in Saudi Arabia.MethodsPatients aged 16 years and older admitted to a participating hospital between October 2018 and August 2024 who received an SOT or a BMT or were diagnosed with a hematological malignancy and had a confirmed CRE infection were included in this retrospective cohort study. A total of 155 eligible patients were included in the study population. The primary outcome of interest was all-cause mortality within 90 days of the date of the first CRE culture.ResultsAmong the 155 patients, 118 (76.1%) had received a solid organ transplant, while 37 (23.9%) had either a bone marrow transplant or a hematological malignancy. The BMT recipients and patients with hematological malignancies were 2.84 times more likely to die within 90 days of their first positive culture [adjusted odds ratio (AOR) = 2.84, 95% confidence interval (CI) = 1.01–8.01, p = 0.049]. Compared to the patients with CRE infections carrying the blaNDM gene, after controlling for other predictors, patients with infections harboring the blaOXA-48 gene were 3.97 times more likely to die within 90 days of the first culture (AOR = 3.97, 95%CI = 1.04–15.15, p = 0.044).ConclusionThe BMT recipients and patients with CRE infections harboring the blaOXA-48 gene were at greater risk for 90-day all-cause mortality in Saudi Arabia, confirming previous findings of high mortality rates associated with CRE infections in immunocompromised populations.